Neurogenic hypertension and the secrets of respiration - Machado, Benedito H.; Zoccal, Daniel B. [UNESP]; Moraes, Davi J. A. (Amer Physiological Soc, 2017)
Despite recent advances in the knowledge of the neural control of cardiovascular function, the cause of sympathetic overactivity in neurogenic hypertension remains unknown. Studies from our laboratory point out that rats submitted to chronic intermittent hypoxia (CIH), an experimental model of neurogenic hypertension, present changes in the central respiratory network that impact the pattern of sympathetic discharge and the levels of arterial pressure. In addition to the fine coordination of respiratory muscle contraction and relaxation, which is essential for O-2 and CO2 pulmonary exchanges, neurons of the respiratory network are connected precisely to the neurons controlling the sympathetic activity in the brain stem. This respiratory-sympathetic neuronal interaction provides adjustments in the sympathetic outflow to the heart and vasculature during each respiratory phase according to the metabolic demands. Herein, we report that CIH-induced sympathetic over activity and mild hypertension are associated with increased frequency discharge of ventral medullary presympathetic neurons. We also describe that their increased frequency discharge is dependent on synaptic inputs, mostly from neurons of the brain stem respiratory network, rather than changes in their intrinsic electrophysiological properties. In perspective, we are taking into consideration the possibility that changes in the central respiratory rhythm/pattern generator contribute to increased sympathetic outflow and the development of neurogenic hypertension. Our experimental evidence provides support for the hypothesis that changes in the coupling of respiratory and sympathetic networks might be one of the unrevealed secrets of neurogenic hypertension in rats.
Keywords: neurogenic hypertension; sympathetic overactivity; presympathetic neurons; respiratory neurons; autonomic and respiratory networks